KEY ASPECTS OF BREDDING AND SEED WORK WITH BUCKWHEAT IN PODILLIA - Вільчинська, Людмила; Гораш, Олександр; Климишена, Ріта; Ляльчук, Петро; Бойко, Олег (SWorldJournal, 2026)
The key aspects of breeding and seed work with buckwheat in Podillia were analyzed. The distribution of samples of the collection of the genus Fagopyrum Mill of the National Heritage is indicated. The main assortment of varieties of Podillia selection fro